KORELASI KETERAMPILAN MEMBACA PEMAHAMAN TEKS EKSPOSISI DENGAN KETERAMPILAN MENULIS TEKS EKSPOSISI SISWA KELAS X SMA NEGERI 7 PADANG - M. Hafrison, Novia, Tressyalina, (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2017)
The purpose of this study is to analisis correlation between comprehension reading skill of exposition text and writing skill of text exposition for students at class X SMAN 7 Padang. The type of this stud was quantitative research with descriptive method and correlation design. Population in this study was students at class X SMAN 7 Padang that enrolled in year of school 2016/2017. Sample in study was determined by application of random sampling technique. Based on study finding, it was concluded that there was a significant correlation between comprehension reading skill of exposition text and writing skill of text exposition for students at class X SMAN 7 Padang with deliberate degree n-1 and confident level of 95%; tcount > ttable (3.58 > 1.68). Therefore, writing skill of text exposition has a correlation with comprehension reading skill of exposition text or student need to comprehend the exposition text to write it.Kata kunci: korelasi, membaca pemahaman, menulis, teks eksposisi